A gestão da informação e as transformações do trabalho na percepção dos trabalhadores: estudo de caso do sistema logístico de uma empresa têxtil de Minas Gerais - Silvia Menezes Pires Dias (2006)
This work results from a research that analyzes changes in a company of textile industry located in Minas Gerais, Brazil. We had two main goals: 1. investigate how the company, in modernization process, due to the globalização and productive restructuring, manages information inside it in a process known as information management; 2. discuss what are (dis)advantages has this administration brought to the workers and what are the real possibilities of theirs effective participation, while subjects, in that process. Two elements were constituted as explanatory basis to this dissertation. First of them concerns to the chosen sector of study Minas Gerais textile industry for its importance as pioneer in the industrialization process, for its revenue and for generated jobs. It is a complex sector, with growth tendency and of continuous modernization. It represents the fourth more important economical activity in world level. The second element concerns the theoretical background of work. It is showed for the information management while managerial and organizational construction, a consequence of transformations of technology and of the world of the work, allied to the configurations of the culture and of the power that bound chosen organization. The general objective of this study was, face to the current context of productive restructuring and due to a historical and daily reality characterized by outstanding elements of the Brazilian culture, to investigate forms for what information management is concept and disseminated in organizational environment and the way as it is perceived theirs articulation (or their contradictions) with the management practices in the company.